3D printable low density B2+BCC refractory element based complex concentrated alloy with high compressive strength and plasticity. (1st March 2023) - Chesetti, Advika; Banerjee, Sucharita; Dasari, Sriswaroop; Nartu, Mohan Sai Kiran; Varahabhatla, S.M.; Sharma, Abhishek; Ramakrishnan, Abhishek; Satko, Daniel; Gorsse, Stephane; Salem, Ayman; Banerjee, Rajarshi
Abstract: While complex concentrated alloys (CCAs), involving large fraction of refractory elements, are promising candidates for structural applications, their relatively high densities,  processing challenges, and low plasticity, has retarded their development. Here,  we report a 3D printable low-density precipitation strengthened CCA, Al10 Nb15 Ta5 Ti30 Zr40 . The chemical homogeneity in the alloy deposited using laser bed powder fusion process is substantially better as compared to as-cast ingot. This homogeneity is attributed to the enhanced solubility at the high temperatures experienced during laser melting, small melt pool dimensions, and the high cooling rates. The as-built CCA exhibited an excellent balance of room temperature mechanical properties, a compressive yield stress ∼1400 MPa, peak stress ∼1700 MPa, and plastic strain exceeding 45%. These properties can be attributed to its unique as-processed microstructure consisting of refined grains incorporating a high density of sub-grain boundaries, containing a nanoscale two-phase mixture of an ordered B2 and disordered BCC solid solution phases. Graphical abstract: Image, graphical abstract